Qualidade da água, impactos e contribuições para a gestão ambiental do Rio Preto, município de Santa Rita, Paraíba. - Eiras, Raquel Cruz de França (2018)
The diverse uses given to water have intensified the environmental impacts on aquatic ecosystems. Poorly planned urban development is undoubtedly the greatest cause of damage to rivers through the launching of domestic and industrial effluents, among other human activities capable of promoting disastrous changes in the natural environment. Throughout the world, announcements regarding the crisis of drinking water shortages have warned of the need to implement a new development model that aims to improve the quality of life and the environment for present and future generations. In Brazil, faced with the reality experienced, several legal instruments have emerged with the intention of promoting environmental management that aims to cover the need of the population in general and preservation and conservation of the environment. The Water Law, in turn, has brought several changes to the management of water resources and is an important ally for the treatment of urban rivers and for the implementation of an effective environmental management, especially at the municipal level. Due to the great importance of water and its conservation for the maintenance and quality of life, the study aims to analyze the water quality of Preto river in Santa Rita, Paraíba, to investigate the main impacts and propose solutions. For water quality analysis, water samples were collected at previously defined points. The analyzed variables were: chlorophyll-a, total phosphorus, orthophosphate, nitrogen compounds (ammonia, nitrate and nitrite), dissolved oxygen, pH, electrical conductivity and the zooplankton community as indicator of water quality. The parameters that have limits pre-established in the CONAMA Resolution (357/05), had the results compared with the classification in which the Preto river is classified (class 3 of fresh water). The main impacts to which the river is subject during its entire course have also been raised, with the purpose of describing and presenting mitigating proposals and reducing the present socioenvironmental conflicts. The water quality monitoring results showed that some parameters indicate releases of untreated effluents and that total phosphorus, pH, and dissolved oxygen presented nonconformity values at some points evaluated according to the resolution for water class in which the river is classified. The Trophic State Index (TSI), was also classified in some points as hypereutrophic. Biomonitoring of water quality has shown that the environmental impacts along the course of the river have reflected on the structure of the zooplankton community. Environmental education, in turn, is embedded in the entire context of transformation in which the country is located, and must be mentioned and valued. In order to do so, formal and non-formal environmental education activities were developed through lectures and field activities in order to sensitize and encourage residents about the environmental problems they face. It is seen, the need to implement corrective measures so that Preto river has adequate characteristics for which it is intended.